Arcaísmos em Guimarães Rosa - Lívia Suassuna (Filologia e Linguística Portuguesa, 1999)
In this paper, we discuss, initially, language mutability and historicity, based on the conception of language as a historical practice and as way of action, and in Eugenio Coseriu’s theory about language changing. In this last case, the theory is shown in its main oppositions with the classical Saussure’s dichotomies. Then, we overviewed the literature to verify different aspects of the phenomenon of archaism as manifestation of language change and stylistic mark. Based upon these theoretical frameworks, we show examples of some archaisms employed by João Guimarães Rosa in two of his works – Grande sertão: veredas and Primeiras estórias. The conclusions of our research indicate that Rosa’s archaisms, beyond old popular or regional speech, is a process of meaning creation and recriation, which represents the permanent and potential language instability, a rupture of historically established patterns, thus confering literary status to his extensive work.